Comparative Study of the Influence of Student Learning Motivation on Student Learning Outcomes in a View of Gender in Thematic Subject - Karyaningsih Karyaningsih; Everhard Markiano Solissa; Emy Yunita Rahma Pratiwi; Dina Destari; Fitria Meisarah (research, training and philanthropy institution Natural Aceh, 2023)
The objectives to be achieved in this study are, 1) to determine the effect of student motivation on student learning outcomes of the male sex in the Thematic subject in class V SDN 52 Bengkulu City. 2) to determine the effect of student learning motivation on student learning outcomes of the female gender in thematic eyes. 3) to determine the effect of student learning motivation on student learning outcomes in thematic subjects and 4) to determine the comparative test results of student learning motivation and student learning outcomes in terms of gender in thematic subjects. This research is a quantitative research with a quantitative descriptive research design with regression and comparison types, sampling was carried out using a non-probability sampling technique. The results of this study are that there is an influence of student learning motivation on student learning outcomes of male and female gender in thematic subjects in class V SDN 52 Bengkulu City. And there are differences in the learning motivation of male and female students.